Monotonicity and Nash implementation in matching markets with contracts - Claus-Jochen Haake; Bettina Klaus (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
We consider general two-sided matching markets, so-called matching with contracts markets as introduced by Hatfield and Milgrom (2005), and analyze (Maskin) monotonic and Nash implementable solutions. We show that for matching with contracts markets the stable correspondence is monotonic and implementable (Theorems 1 and 3). Furthermore, any solution that is Pareto efficient, individually rational, and monotonic is a supersolution of the stable correspondence (Theorem 2). In other words, the stable correspondence is the minimal solution that is Pareto efficient, individually rational, and implementable.
urn:nbn:de:hbz:361-7662
Keywords: C62; C78; D78; J41; 330; Matching with Contracts; (Maskin) Monotonicity; Nash implementation; Stability; Personalbeschaffung; Arbeitsvertrag; Nash-Gleichgewicht; Gleichgewichtstheorie; Theorie